Plasma Acylcarnitines Are Associated With Physical Performance in Elderly Men - Lum, Helen (Oxford University Press, 2011)
BACKGROUND. Metabolic profiling might provide insight into the biologic underpinnings of disability in older adults. METHODS. A targeted mass spectrometry–based platform was used to identify and quantify 45 plasma acylcarnitines in 77 older men with a mean age of 79 years and average body mass index of 28.4 kg/m(2). To control for type I error inherent in a test of multiple analytes, principal components analysis was employed to reduce the acylcarnitines from 45 separate metabolites, into a single “acylcarnitine factor.” We then tested for an association between this acylcarnitine factor and multiple indices of physical performance and self-reported function. RESULTS. The acylcarnitine factor accounted for 40% of the total variance in 45 acylcarnitines. Of the metabolites analyzed, those that contributed most to our one-factor solution were even-numbered medium and long-chain species with side chains containing 10–18 carbons (factor loadings ≥0.70). Odd-numbered chain species, in contrast, had factor loadings 0.50 or less. Acylcarnitine factor scores were inversely related to physical performance as measured by the Short Physical Performance Battery total score, two of its three component scores (gait and chair stands Short Physical Performance Battery), and usual and maximal gait speeds (ρ = −0.324, −0.348, −0.309, −0.241, and −0.254, respectively; p < .05). CONCLUSIONS. Higher acylcarnitine factor scores were associated with lower levels of objectively measured physical performance in this group of older, largely overweight men. Metabolic profiles of rodents exhibiting lipid-induced mitochondrial dysfunction show a similar phenotypic predominance of medium- and long-chain acylcarnitines.